2004
DOI: 10.2196/jmir.6.3.e29
|View full text |Cite
|
Sign up to set email alerts
|

Internet Versus Mailed Questionnaires: A Randomized Comparison

Abstract: Background The use of Internet-based questionnaires for collection of data to evaluate patient education and other interventions has increased in recent years. Many self-report instruments have been validated using paper-and-pencil versions, but we cannot assume that the psychometric properties of an Internet-based version will be identical.Objectives To look at similarities and differences between the Internet versions and the paper-and-pencil versions of 16 existing self-report instruments useful in evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
223
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(250 citation statements)
references
References 16 publications
13
223
2
7
Order By: Relevance
“…Self-report questionnaires obtained online are similar to written questionnaires in terms of reliability and validity, 21 as shown for depression scales including the Beck Depression Inventory (BDI). 22 The primary endpoint of the study was severity of depressive symptoms as measured by the BDI.…”
Section: Discussionmentioning
confidence: 98%
“…Self-report questionnaires obtained online are similar to written questionnaires in terms of reliability and validity, 21 as shown for depression scales including the Beck Depression Inventory (BDI). 22 The primary endpoint of the study was severity of depressive symptoms as measured by the BDI.…”
Section: Discussionmentioning
confidence: 98%
“…The first is the relatively small sample size recruited on the Internet, which was probably more heterogeneous and may have resulted in a selection bias producing the underrepresentation of specific groups of people or meditation types, even though some studies confirm the reliability of data obtained from this source (Ritter, Lorig, Laurent, & Matthews, 2004). Second, indicators of meditation practice were reported through a recall method.…”
Section: Discussionmentioning
confidence: 99%
“…Ritter, Lorig, Laurent, and Matthews (2004) compared the psychometric properties of Internet-based versus mailed paper-and-pencil questionnaires. They found that questionnaires administered through the Internet were reliable and answered as often as the paper-and-pencil questionnaire.…”
Section: Discussionmentioning
confidence: 99%